The moderating effects of basic needs satisfaction at work on the relationships between burnout, work-family conflict and organizational commitment: relevance of the Conservation of Resources (COR) theory - Mohd Shuhaimi, Suzalina; Marzuki, Najib Ahmad (MCSER Publishing, Rome-Italy, 2015)
In this modern era of competitiveness, work commitment is imperative as every organization strive to excel.Employees must find the means to achieve goals with full determination and commitment despite their personal difficulties. This paper analyses the moderation effect of the dimensions of basic needs satisfaction at work (autonomy, relatedness, and competence) on the relationships between burnout (exhaustion, professional efficacy, and cynicism), work-family conflict (work interfering with family (WIF), family interfering with work (FIW)), and the dimensions of organizational commitment (affective, continuance and normative).Two hundred and twenty administrative and professional groups from Kuala Lumpur City Hall (KLCH), Malaysia were involved in the study. The data gathered was examined using hierarchical multiple regression analysis to determine the moderating effects between variables.The findings revealed that: (1) autonomy moderates the relationships between exhaustion and continuance commitment; and (2) relatedness moderates the relationships between WIF and continuance commitment.The study has defined the motivating factors using the Conservation of Resources (COR) theory as a foundation for the discussion.Recommendations and areas for future research are also discussed.